Receiving and Detection of Ultra-Wideband Microwave Signals Radiated by Pulsed Excitation of Monopole Antennas - Steponas AŠMONTAS; Oleg KIPRIJANOVIČ; Boris LEVITAS; Jonas MATUZAS; Irina NAIDIONOVA (Medžiagotyra, 2014)
Pulsed excitation of small size monopole antennas for generating wideband electromagnetic pulses was used. The monopoles were excited by electrical pulses having rise times of 600 ps, 200 ps, 70 ps and voltages 100 V, 15 V, and 0.4 V respectively. Antennas spanning (0.3 – 26) GHz bandwidth, including broadband horns with coaxial outputs, were employed to receive signals, which were investigated using (0 – 26) GHz passband sampling oscilloscope. It was found that waveforms of signals, received by the antennas, mostly depend on the pulse rise time and on the details of geometry of monopoles. The electromagnetic pulses have relatively long duration of about 30 ns and spectral harmonics up to 22 GHz. Therefore they can be attributed to pulses with large base. The results show that the upper frequencies of the spectrum most probably are cut off by existing arrangement. Usage of such pulses can find wide practical application when they are received after transmission trough different media by a number of antennas having different operational frequency ranges, followed by digital signal processing. DOI: http://dx.doi.org/10.5755/j01.ms.20.2.6330